2002
DOI: 10.1161/01.str.0000016973.80180.7b
|View full text |Cite
|
Sign up to set email alerts
|

Increased Anisotropy in Acute Stroke

Abstract: Background and Purpose-The increase in fractional anisotropy (FA) in acute stroke has yet to be explained. Using an engineering methodology known as pq diagrams, we sought to explain the increase in FA by describing changes in the total magnitude of the diffusion tensor (L) as well as the isotropic (p) and anisotropic (q) components. Methods-Diffusion tensor imaging was performed in 10 patients with stroke Ͻ27 hours old. The diffusion tensor was decomposed into the p and q components and plotted to describe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 22 publications
3
66
1
Order By: Relevance
“…For major WM tracts, diffusion anisotropy was elevated in 4/8 patients r7 h after stroke onset (mean rFA = 1.2070.16 (P < 0.01) in these 4 patients) and 0/13 patients > 7 h. Subcortical WM in the gyri showed similar elevated rFA findings in 4/7 patients r7 h (mean rFA = 1.1770.21 (P < 0.01) in these 4 patients) and 0/12 patients > 7 h. Our findings are in agreement with five human DTI studies that have reported elevations of FA less than 6 h (13% to 21% rise) (Green et al, 2002;Ozsunar et al, 2004a, b;Schaefer et al, 2003;Yang et al, 1999). However, one study had 3 patients less than 6 h with only 1 showing elevated FA (Green et al, 2002), and another acquired only 3-direction diffusion-wt images in the majority of their patients (Yang et al, Figure 1 T 2 -weighted images (T2W; b = 0 sec/mm 2 ), isotropic diffusion-weighted images (DWI; b = 1000 sec/mm 2 ), Trace/3 apparent diffusion coefficient (ADC) maps, and fractional anisotropy (FA) maps from 2 patients depicting hyperacute (patient 1; 2 h postsymptom onset) and acute (patient 18; 14 h postsymptom onset) infarcts in the middle cerebral artery distribution involving major white matter (WM) tracts and subcortical WM regions (refer to Table 1). Over 19 slices in patient 1 (51-year-old male patient), 75% of the major WM regions-of-interest (ROIs) evaluated showed an increase in rFA, whereas 25% showed reductions in rFA.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For major WM tracts, diffusion anisotropy was elevated in 4/8 patients r7 h after stroke onset (mean rFA = 1.2070.16 (P < 0.01) in these 4 patients) and 0/13 patients > 7 h. Subcortical WM in the gyri showed similar elevated rFA findings in 4/7 patients r7 h (mean rFA = 1.1770.21 (P < 0.01) in these 4 patients) and 0/12 patients > 7 h. Our findings are in agreement with five human DTI studies that have reported elevations of FA less than 6 h (13% to 21% rise) (Green et al, 2002;Ozsunar et al, 2004a, b;Schaefer et al, 2003;Yang et al, 1999). However, one study had 3 patients less than 6 h with only 1 showing elevated FA (Green et al, 2002), and another acquired only 3-direction diffusion-wt images in the majority of their patients (Yang et al, Figure 1 T 2 -weighted images (T2W; b = 0 sec/mm 2 ), isotropic diffusion-weighted images (DWI; b = 1000 sec/mm 2 ), Trace/3 apparent diffusion coefficient (ADC) maps, and fractional anisotropy (FA) maps from 2 patients depicting hyperacute (patient 1; 2 h postsymptom onset) and acute (patient 18; 14 h postsymptom onset) infarcts in the middle cerebral artery distribution involving major white matter (WM) tracts and subcortical WM regions (refer to Table 1). Over 19 slices in patient 1 (51-year-old male patient), 75% of the major WM regions-of-interest (ROIs) evaluated showed an increase in rFA, whereas 25% showed reductions in rFA.…”
Section: Discussionsupporting
confidence: 90%
“…However, studies reporting changes in FA have been variable with either reductions (Munoz Maniega et al, 2004;Sorensen et al, 1999), elevations (Schaefer et al, 2003), a mixture of changes (Green et al, 2002;Ozsunar et al, 2004a, b;Yang et al, 1999), or no change (Harris et al, 2004). Elevations of 8% to 45% in FA have been noted to occur from < 4 h up to 24 h after symptom onset (Green et al, 2002;Ozsunar et al, 2004a;Schaefer et al, 2003;Yang et al, 1999). Interestingly, similar studies have also reported FA reductions of 2% to 44% in individual patient data from 4 h up to 27 h after symptom onset (Green et al, 2002;Yang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the way in which FA is calculated, proportional differences in the Euclidian magnitude of a tensor and the magnitude of its anisotropic component will result in the same FA value (Green et al, 2002) and consequently a given FA value will not be unique. This introduces a certain level of ambiguity in the interpretation of FA values for O.A.…”
Section: Diffusion Segmentation (Dseg) Techniquementioning
confidence: 99%
“…While FA and MD are the most popular scalar measures in clinical research, in [17,18] plotting the FA in the region of interest (ROI) on a (|M I | F , |M A | F )-plane is seen to be useful. So far, all the scalars in this section have been pointwise measures, that is they contain information only on the diffusion tensor in a particular voxel.…”
Section: Scalar Measures In Dtimentioning
confidence: 99%